PENGARUH JUMLAH TENAGA KERJA DAN LUAS LAHAN TERHADAP EKSPOR KOPI DAN PRODUKTIVITAS KOPI PROVINSI BALI - Ketut Sutrisna, Ni Kadek Diana Arta Pertiwi (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Supporter of the economy International trade, the Province Bali engaged in agricultural export activities which one of the milestones to improve the country's economy, especially in the coffee commodity. Bali Coffee is one of the coffee produced in the Province Bali and is a coffee that is quite in demand, the Province Bali is able to ship coffee abroad or exports in the period 2011-2018 the last year continues to experience an increase but dropped in 2018. The purpose of this study for examine are the effect of labor force, land area and coffee productivity on Bali Province coffee exports in 2011-2018. This study uses secondary data sourced from the Bali Provincial Holticultural Agriculture Office and the Bali Provincial Trade and Industry Office and then analyzed using a path analysis and the sobel test based on the analysis obtained the number of workers and land area has a positive effect on coffee productivity but only the number of workers work that has no significant effect. Coffee productivity variable is an intervening variable indirect effect of the variable number of labor and land area on the export of Bali Province coffee. keyword: number of labor, land area, coffee productivity, coffee exports.